A green path towards sustainable development: Optimal behavior of the duopoly game model with carbon neutrality instruments. (29th April 2022) - Hussain, Jafar; Lee, Chien‐Chiang
Abstract: Carbon emission is a global issue, and China is facing many problems to resolve it, especially in emission‐generating companies (EGCs). To maintain sustainable development, it is necessary to reduce carbon emissions for the well‐being of society, and carbon neutrality can play an important role. With China targeting the goal of carbon neutrality to reduce carbon emissions, this research aims to bridge the gap in the literature by considering carbon neutrality instruments in a duopoly market. The study sets up a mathematical model of the duopoly game to achieve desired objectives and then applies a simulation‐based optimization technique to examine the mathematical model under different experiments. After manipulating various scenarios to find the optimal values of carbon neutrality instruments, the results indicate that green bond provision, emission tax, and emission quota play a vital role in carbon neutrality. Different combinations of carbon neutrality instruments reduce various levels of carbon emissions. We further show that a combination of emission tax upon EGCs plays a key role in reducing carbon emissions during the fifth scenario. In the second scenario, a combination of green bond provision and emission tax reduces carbon emissions, but is lower than the fifth scenario. This research offers a reference for policymakers to move towards carbon neutrality, and it is beneficial for the government to decide the optimal values of carbon neutrality instruments.